Social Media Marketing to Brand Awareness in Private University - Malik Akbar Rohandi, Mochamad; Nur Hasanah, Eneng; Tresna Gumilar, Eka (KnE Social Sciences, 2023)
Social media can be used as a selling strategy, services, communication, and a source of information. This research aims to measure the impact of digital marketing using four different social media, that is. Youtube, Facebook, Instagram, and Twitter through brand awareness in the private universities in Indonesia based on how the user gets information from social media and makes it the information source. The methodology used in this research is the quantitative method of causal effect. This research was conducted by using primary and secondary data. The sampling technique uses non-probability sampling by using minimum respondents from Bernoulli. While, the data analysis was done using path analysis. By using 385 respondents, the research shows that digital marketing simultaneously influences university brand awareness by 22.96%. This result shows that digital marketing is one of the media which can be used to increase public brand awareness through university. Meanwhile, Facebook and Twitter have a positive influence on university brand awareness. In conclusion, Facebook and Twitter can increase the brand awareness of a university. Keywords: digital marketing; social media; brand awareness; private university